1985
DOI: 10.1016/s0735-1097(85)80361-2
|View full text |Cite
|
Sign up to set email alerts
|

Regional coronary vasoconstriction after combined beta-adrenergic and calcium channel blockade in patients with coronary artery disease

Abstract: The beta-adrenergic and calcium channel blocking drugs, which individually and combined have proven efficacious in the treatment of angina pectoris, appear to have opposing effects on coronary artery vasomotion. Previous studies have shown that beta-adrenergic blockade may potentiate and calcium channel blockade reverse coronary vasoconstriction during adrenergic cold stimulation in patients with coronary artery disease. To assess the coronary hemodynamic effects of combined drug therapy, thermodilution corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…Previous data from Kern et al 22,23 have suggested that ␤-blockers (intravenous propranolol) could potentiate coronary vasoconstriction in patients with coronary artery disease undergoing a cold pressor test because of an unopposed ␣-adrenergic vasomotor tone. On the contrary, Gaglione et al 24 showed a significant vasodilation of stenotic coronary arteries after intracoronary propranolol in patients undergoing supine bicycle stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from Kern et al 22,23 have suggested that ␤-blockers (intravenous propranolol) could potentiate coronary vasoconstriction in patients with coronary artery disease undergoing a cold pressor test because of an unopposed ␣-adrenergic vasomotor tone. On the contrary, Gaglione et al 24 showed a significant vasodilation of stenotic coronary arteries after intracoronary propranolol in patients undergoing supine bicycle stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol augments the coronary vasoconstrictive response elicited in coronary patients by the cold pressor test.8 9 Theoretically, diltiazem might be expected to be a better antianginal drug in a cold environment because it is a coronary vasodilator, in contrast to propranolol. In this study, both propranolol and diltiazem delayed the onset of ischemia during exercise at both -8°and 200 C. This beneficial effect at normal temperatures is quantitatively similar to results of previous studies.17 The antianginal efficacy of these drugs has not been investigated at low temperatures.…”
Section: Effect Ofantianginal Drugsmentioning
confidence: 99%
“…,B-Adrenergic-blocking drugs potentiate the coronary vasoconstriction induced at the site of atherosclerotic lesions by the cold pressor test.8 9 In contrast, nifedipine blocks this response. 10 The efficacy of antianginal drugs has not been assessed in a cold environment.…”
mentioning
confidence: 99%
“…При этом есть и противоположные патофизиологические аспекты такого взаимодействия. Например, БКК противодействуют коронарной вазоконстрикции, вследствие применения БАБ, что может увеличить перфузию только в неишемизированных областях и может уменьшить кровоток в зонах ишемии [4,5]. Увеличение риска ишемии миокарда и ухудшение течения стенокардии при применении такой комбинации также возможно вследствие потенцирования гипотензивного действия [6], увеличения нагрузки на стенку левого желудочка (ЛЖ) или выраженной брадикардии [7,8].…”
Section: мнение по проблемеunclassified